State University’s Institusional Repository as a Storage for Civitas Academia Intelectul Property - Dyah Puspitasari Srirahayu (Record and Library Journal, 2015)
Many works - works the academic community that has not been published so that the intellectual property  of  an  educational  institution  is  not  widely  known  by  the  general  public.  Institutional repository  created  and  used  to  manage  the  results  of  these  works  that  can  be  accessed  by  all people.  This  study  aimed  to  describe  the  institutional  repository  of  high  perguruang  country  in Java  Timursebagai  container  to  the  intellectual  academic  community  views  of  content,  the software  used  unit  that  houses,  and  ratings  on  Webometrik.  This  study  uses  a  quantitative approach  with  descriptive  methods.  The  population  used  in  this  study  are  all  the  institutional repository of public universities in East Java, which already are online. The sampling technique is the total sampling. The results of this study found that 50% of state universities in East Java has an  IR that can be accessed via the internet, 100% of existing  IR content is scientific output, the software used various existing GDL, DSpace, Eprints and others, and IR state universities in Java East 66.7% was ranked in webometrik.